Fred Claus - Dobkin, David, 1969-; Nelson, Jessie; Silver, Joel.; Fogelman, Dan.; Vaughn, Vince; Giamatti, Paul.; Higgins, John Michael; Richardson, Miranda; Weisz, Rachel, 1971-; Bates, Kathy, 1948-; Ludacris (Rapper); Banks, Elizabeth, 1974-; et al. (Burbank, Calif. : Warner Home Video, 2008)
Fred Claus has lived in his little brother's shadow for most of his life. Fred is in jail and Nicholas has to bail him out on the condition he come to the North Pole and repay his debt.
Widescreen and full screen.
Director of photography, Remi Adefarasin ; editor, Mark Livolsi ; music, Christophe Beck ; costume designer, Anna Sheppard ; production designer, Allan Cameron.
Vince Vaughn, Paul Giamatti, John Michael Higgins, Miranda Richardson, Rachel Weisz, Kathy Bates, Ludacris, Elizabeth Banks, Kevin Spacey.
MPAA rating: PG; for mild language and some rude humor.
DVD; Dolby Digital.
English dialogue, French or Spanish subtitles; subtitles for the deaf and hard of hearing (SDH)
Keywords: Santa Claus -- Drama; Brothers -- North Pole -- Drama; Debt -- Drama; Christmas films; Comedy films; Feature films; Films for the hearing impaired